2006
DOI: 10.1021/ol0608404
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Transannular Cyclization Products of Sarcophytoxide, a 14-Membered Marine Cembranoid:  Anomalous Stereochemistry of Epoxide−Ketone Rearrangement

Abstract: [reaction: see text] Treatment of sarcophytoxide with trimethylsilyl trifluoromethanesulfonate afforded an aromatic ketone as an unusual cyclization product. The modified Mosher's method and X-ray analysis performed on the aromatic ketone revealed that it is a 4:1 mixture of 8(R)- and 8(S)-enantiomers. It also suggested that the precursor ketone has 8(R)-configuration, which is contradictory to that expected from the ordinary epoxide-ketone rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Fortunately, the minor ketone (À)-5 was crystallized and the crystal was subjected to X-ray analysis, determining the structure to be 5 (relative). 8 The X-ray crystallography also revealed that the crystal applied to the analysis was racemic, that is, a racemate crystallized out from (À)-5. The smaller ½ D absolute value (67) of (À)-5 than that of (+)-5 (75) suggests that this material is enantiomerically impure [enantiomeric excess (ee) of (À)-5: 79% based on the ½ D value of (+) -5].…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, the minor ketone (À)-5 was crystallized and the crystal was subjected to X-ray analysis, determining the structure to be 5 (relative). 8 The X-ray crystallography also revealed that the crystal applied to the analysis was racemic, that is, a racemate crystallized out from (À)-5. The smaller ½ D absolute value (67) of (À)-5 than that of (+)-5 (75) suggests that this material is enantiomerically impure [enantiomeric excess (ee) of (À)-5: 79% based on the ½ D value of (+) -5].…”
Section: Resultsmentioning
confidence: 99%
“…C-17). Based on the physicochemical analyses, including IR, 1D NMR, MS, and their comparisons with data from the literature, the isolated compound was determined to be a known cembranoid typediterpene, (2S,7S,8S)-sarcophytoxide (Bowden, Coll, Heaton, Konig & Scheuer, 1987;Nii et al, 2006;Pollastro et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…46 Several tetrasubstituted cyclopentanes (51) can be prepared in four steps from cyclopentadiene in good overall yield (30%) by the acid-catalysed rearrangement of epoxide (49) followed by a regio-and stereo-selective nucleophilic attack, with control of the relative configuration of four contigous stereogenic centres in a single operation (Scheme 14). 54 The concomitant opening of the epoxide ring in (61) creates flexibility, thereby permitting intermolecular ring closure. The Lewis acid-promoted rearrangement of 2,2,3,3-tetrasubstituted de 2,3-epoxyalcohol derivatives, which have only a slight difference in stability of carbocation at the C(2) or C(3) positions, proceeds through the C(3) carbocation.…”
Section: Cationic Rearrangementsmentioning
confidence: 99%